CENTRAL ASIA IN SEARCH FOR ITS OWN WAY OF INTEGRATION - E. V. Makhmutova (Vestnik MGIMO-Universiteta)
The article deals with perspectives for integration within Central Asian region. The existing experience of integration in the region is perceived as an important factor. Currently the discourse of regional integration is gaining ground in Central Asia. It can be seen by the updates in the foreign policy concepts of most of the post-Soviet Central Asian countries. Another driver of the issue is the growing international activity of Uzbekistan which is due to the new President of the republic elected in 2016. The article defines the context of regional development, challenges which the region face, specific traits of political process.The rationale for integration is linked to economic problems which cannot be solved by each Central Asian country on its own. Construction of any transport and logistical infrastructure in the region as well as tackling security threats determine regional cooperation. Although the researchers give arguments for advantages of integration in the region, Central Asian leaders are still looking for more efficient format of interregional cooperation. This process is not linear with its ups and downs. The article reveals the institutional experience that Central Asia gained over 1990s in search for its own integration project. Today this experience can be treated as an important step to maturity of national governance in the region.But the reason why there is no implementation of integration initiatives discussed in the region earlier is that the current Central Asian political elites are not favorable to any kind of cooperation that will lead in the future to the formation of supranational bodies in the region. They perceive it as a threat to a stable national development. Another factor is a higher commitment of Central Asian countries to cooperate with non-regional economies rather than within the region. In such context a strategy of “bandwagoning” (as it describes S. Walt) will hamper any regional integration project.